Upaya Guru IPS dalam Meningkatkan Gemar Membaca Siswa Kelas IX di SMPN 2 Kepung Kabupaten Kediri - Umi Nur Atni Setyaningsih; Dita Hendriani (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research is motivated by the decline in students’ interest in reading. Therefore, social studies teachers play a role in guiding and fostering student to become students who love to read given the importance of reading in life. This research uses a descriptive qualitative approach. The data collection techniques used were observation, interviews, and documentation. Observation is used to observe activities in SMPN 2 Kepung Kediri Regency, interviews and documentation are used to explore information about the problem under study, as well as school document data. The result showed that : is by motivating students by using simple and relaxed learning but still monitor students well, giving a good example to students. Teachers also give appreciation to students such as giving grades, praise, and videoing students when presenting. In addition, the teacher’s efforts are as a classroom manager, the teacher ensure students are in the classroom, ensure the cleansliness and comfort of the classroom, and strives for learning to run well. The supporting factors namely the teacher creates a pleasant of reading book facilities made tosupport student learning. The inhibiting factor is the focus of students who began to decline in the middle of learning, the ability of different students – different and there are student who are lazy.